2010
DOI: 10.7202/038923ar
|View full text |Cite
|
Sign up to set email alerts
|

Cinétique de phototransformation de polluants organiques émergents en solution aqueuse diluée

Abstract: Les vitesses de phototransformation de quatre hormones (estradiol, éthinylestradiol, progestérone, testostérone) et de deux anti-inflammatoires non stéroïdiens (diclofénac et naproxen) ont été étudiées en milieu aqueux dilué. Les expériences de photolyse ont été réalisées sous irradiation monochromatique (254 nm) et sous irradiation polychromatique (λ > 280 nm). Les résultats expérimentaux ont montré que les rendements quantiques de photodécomposition sont faibles (entre 0,02 et 0,08) à l’exception du diclofén… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…This fact is in agreement with Meite's results (Meite et al, 2010) who reported that the value of the quantum yield of naproxen photolysis at 254 nm, estimated by using a simple model of the type Ln½C=½C o ¼ À2:3$ε l $[$F l $I o ðlÞ ¼ Àk app $t, increases at increasing oxygen concentration in the liquid bulk. This observation may explain the discrepancies found in the literature for naproxen quantum yield values reported by different Authors (Meite et al, 2010;Benitez et al, 2009;Pereira et al, 2007a,b).…”
Section: 2supporting
confidence: 91%
See 4 more Smart Citations
“…This fact is in agreement with Meite's results (Meite et al, 2010) who reported that the value of the quantum yield of naproxen photolysis at 254 nm, estimated by using a simple model of the type Ln½C=½C o ¼ À2:3$ε l $[$F l $I o ðlÞ ¼ Àk app $t, increases at increasing oxygen concentration in the liquid bulk. This observation may explain the discrepancies found in the literature for naproxen quantum yield values reported by different Authors (Meite et al, 2010;Benitez et al, 2009;Pereira et al, 2007a,b).…”
Section: 2supporting
confidence: 91%
“…The values of quantum yields of direct UV 254 -photolysis for NP 1 and NP 2 species were estimated for the first time in the present paper, whereas the value calculated for F NP (1.297$10 À2 AE 1.23$10 À3 mol E À1 ) is in good agreement with that previously reported (1.5$10 À2 AE 5.0$10 À3 mol E À1 ) by Meite et al (2010). From the comparison of the three parameters F NP , F NP1 and F NP2 it can be assessed that, at the same experimental starting conditions, the photoreactivity at 254 nm follows the order: NP > NP 1 > NP 2 even if the order of molar absorptivities is ε 254…”
supporting
confidence: 67%
See 3 more Smart Citations